2014
DOI: 10.1007/s00338-014-1126-5
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the reef manta ray Manta alfredi in eastern Australia

Abstract: The reef manta ray Manta alfredi aggregates at several sites along the east coast of Australia. Photographic identification and mark-recapture methods were used to report on the site affinity, size and structure of this population of M. alfredi. A total of 716 individuals were identified in 1982-2012, including 636 at Lady Elliot Island (LEI), southern Great Barrier Reef. Over 60 % of individuals identified were resighted at least once during the study period. Multiple resightings within and among years imply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
106
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 36 publications
5
106
1
Order By: Relevance
“…It is well-established that M. alfredi exhibits strong migratory behaviour and movements of up to 500 km are not uncommon (Couturier et al, 2011;Germanov & Marshall, 2014;Jaine et al, 2014), with few confirmed dispersals in Australia up to 1150 km . Individual rays have demonstrated affinity for particular sites and regions (Braun et al, 2015;Couturier et al, 2014;Kessel et al, 2017;Marshall et al, 2011), although most photo-ID and tagging studies have focused on populations separated by large distances and/or by regions of deep water (Deakos et al, 2011).…”
mentioning
confidence: 99%
“…It is well-established that M. alfredi exhibits strong migratory behaviour and movements of up to 500 km are not uncommon (Couturier et al, 2011;Germanov & Marshall, 2014;Jaine et al, 2014), with few confirmed dispersals in Australia up to 1150 km . Individual rays have demonstrated affinity for particular sites and regions (Braun et al, 2015;Couturier et al, 2014;Kessel et al, 2017;Marshall et al, 2011), although most photo-ID and tagging studies have focused on populations separated by large distances and/or by regions of deep water (Deakos et al, 2011).…”
mentioning
confidence: 99%
“…Photo-ID has been widely used across taxonomic groups, such as terrestrial and marine mammals (Kelly, 2001;Langtimm et al, 2004), reptiles (Schofield et al, 2008;Gardiner et al, 2014) and fish (Couturier et al, 2014;Kanive et al, 2015). Photo-ID is considered a largely non-invasive method by which animals are initially "captured" in photographs, and subsequently matched through photographic "recaptures" to create an individual's capture history.…”
Section: Introductionmentioning
confidence: 99%
“…Individual manta rays have been identified from patterns of ventral markings in recent studies to assess the population size of M. alfredi in Hawaii (Deakos, Baker & Bejder, 2011), Mozambique (Marshall, Dudgeon & Bennett, 2011c), the Maldives (Kitchen-Wheeler, Ari & Edwards, 2012), and Australia (Couturier et al, 2014), or the seasonal occurrence of M. birostris in Brazil (Luiz et al, 2009). To identify individual manta rays, Luiz et al (2009) and Deakos et al (2011) used the entire ventral pattern of each individual sighted, whereas Marshall et al (2011c) defined the standardized region as a rectangle-shaped area extending posterior from the anterior margins of the anterior gill slits, including the pelvic fins.…”
Section: Introductionmentioning
confidence: 99%
“…The software MANTA MATCHER, used for individual identification, also relies on the spot patterns in the rectangular area on the ventral side, including the spot markings at the end of the gill slits (Town, Marshall & Sethasathien, 2013, Fig. 1A), and the same rectangular area was also used by Couturier et al 2014.…”
Section: Introductionmentioning
confidence: 99%